Implementing the MBKM (Independent Learning–Independent Campus) Curriculum: A Qualitative Case Study in a History Education Program in Indonesia - Gunartati Gunartati; Zulkarnain Zulkarnain; Fini Fajri Mulyani (AL-ISHLAH: Jurnal Pendidikan, 2026)
This study aims to examine the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) curriculum in the History Education Study Program, Faculty of Social Sciences, Law, and Political Sciences, Yogyakarta State University. This research addresses the need to understand how curriculum reform based on student centered and experiential learning is implemented in discipline specific contexts. This study employs a qualitative approach with a descriptive case study design. Participants were selected using purposive sampling and consisted of lecturers and students involved in MBKM activities. Data were collected through observation, in depth interviews, and document analysis, and were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings show that the implementation of the MBKM curriculum has generally been successful in promoting flexible and student centered learning, particularly through the adoption of project based learning and digital based instruction. However, the implementation is still in an adaptive stage, with several challenges identified, including limited student understanding of MBKM mechanisms, coordination issues, and adjustments in the academic system. This study implies that effective implementation of MBKM requires stronger institutional support, clearer communication strategies, and improved program design. The findings contribute to higher education curriculum development by highlighting the importance of aligning policy, pedagogy, and institutional readiness in implementing curriculum reform.